Causes and effects of historical transmission grid collapses and implications for the German power system - Marika Behnert; Thomas Bruckner (Universität Leipzig, Institut für Infrastruktur und Ressourcenmanagement (IIRM), 2018)
Against the background of the energy transition accompanied by a rising penetration of renewable energy (REN) sources and a stepwise phase out of conventional power plants in order to fulfill climate protection targets, the requirements for a reliable transmission grid infrastructure increased in the last years. High coordination and communication efforts among market and system operators as well as weather extremes that occur more frequently enhance the probability of critical network states. In this paper, causes and impacts of 250 prominent transmission grid collapses in the period from 1965 to 2012 were analyzed. Based on historical events, blackout data sets were clustered inter alia by their date, affected continent as well as the duration of interrupted supply, respectively. We find an ascending number of outages along with a longer averaged duration over time. It is studied how different categories of causes evoking large-scale power blackouts are distributed regionally and temporally. Furthermore, challenges to prevent grid malfunctions, both from a technical and societal perspective, are elaborated focusing on the German power system.
Keywords: 330; transmission grid stability; power network blackouts; cascading outages; critical infrastructures